Ludira – Setya – Tresna: Potret Fenomenologi dalam Studi Kasus Lagon Dharma Kasetyan - Lutfi Zibahnul Aziz; Teguh Tri Wahyudi (Universitas Negeri Malang, 2021)
Abstract: Descriptively formulated three objectives in this article consisted of: (1) Portrait of the ludira fragment in the lyrics of the Dharma Kasetyan song, (2) Portrait of the setya fragment in the Dharma Kasetyan song, and (3) The portrait of the Tresna fragment in the Dharma Kasetyan song. A qualitative descriptive research method was used with the data collection techniques for the document studies in the form of compositions of poetry and recordings of performances on the youtube page. The collected data was then dissected using a phenomenological approach that focuses on portraits of Ludira, Setya and Tresna. Based on the data findings and discussion, three conclusions can be drawn. First, the whole fragment contains about dharma (good behavior performed by humans) and loyalty (setya); Second, it is an act of human sacrifice that pours out everything until it bleeds (ludira); and Third, consciously to suffer for love (tresna). The story of loyalty and dharma in life is not only a love story between two lovebirds, a man and a woman, but also the loyalty and love of parents for their children, as well as how loyal they are in keeping their promises. Keywords: dharma kasetyan, phenomenology, ludira, setya, tresna Abstrak: Secara deskriptif dirumuskan tiga hal yang dijadikan tujuan dalam artikel ini terdiri dari: (1) Potret fragmen ludira pada syair lagu Dharma Kasetyan, (2) Potret fragmen setya pada syair lagu Dharma Kasetyan, dan (3) Potret fragmen tresna pada syair lagu Dharma Kasetyan. Metode penelitian deskriptif kualitatif digunakan dengan teknik pengumpulan data studi dokumen berupa komposisi syair dan rekaman pementasan di laman youtube. Data terkumpul selanjutnya dibedah dengan pendekatan fenomenologi yang difokuskan pada potret ludira, setya dan tresna. Berdasarkan temuan data dan pembahasan dapat disimpulkan tiga rumusan. Pertama, keseluruhan fragmennya berisi mengenai dharma (perilaku baik yang dilakukan oleh manusia) dan kesetiaan (setya); Kedua, merupakan tindakan pengorbanan manusia yang mencurahkan segalanya sampai berdarah-darah (ludira); dan Ketiga, dengan sadar untuk menderita karena cinta (tresna). Kisah kesetiaan dan dharma dalam kehidupan tidak hanya cerita cinta antara dua sejoli lelaki dan perempuan, namun juga kesetiaan dan cinta orang tua terhadap anaknya, juga bagaimana kesetiaan dalam memegang teguh pada janji. Kata kunci: dharma kasetyan, fenomenologi, ludira, setya, tresna.